Analisis Yuridis Penerapan Prinsip Mengenal Nasabah (Know Your Customer) sebagai Upaya Penanggulangan Tindak Pidana Pencucian Uang pada Perusahaan Asuransi : (Studi Putusan Nomor 538/PID.SUS/2023/PN.Jkt.Sel) - Fransiska Milenia Cesarianti (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The basic principle of knowing the customer is an important aspect in an insurance company. Insurance companies are required to have guidelines for the principle of knowing the customer in order to analyse prospective customers and monitor transactions made by customers. In the decision study that the author made as the object of research, the result is that the application of the customer principle has not been able to overcome the crime of money laundering. So the importance of internal supervision of the insurance company to more firmly apply the principle of knowing the customer so that then the crime of money laundering can be overcome. Money laundering is an act of disguising illegal actions and then turning them into assets that seem legal. There are many types of initial actions to commit money laundering offences. In this research are: 1) Can the application of the principle of knowing the customer overcome the crime of money laundering in Decision Number 538/Pid.Sus/2023/Pn.Jkt.Sel? (2) What are the obstacles faced in the application of the principle of knowing the customer in Decision Number 538/Pid.Sus/2023/Pn.Jkt.Sel? This research uses normative juridical research. The research approach used is the statutory approach method.